ANALISIS KAIDAH KEBAHASAAN KOMIK DIGITAL WEBTOON ”LUCUNYA HIDUP INI” SERTA IMPLIKASINYA SEBAGAI MEDIA PEMBELAJARAN TEKS ANEKDOT PADA JENJANG SEKOLAH MENENGAH ATAS - Tania Dwitayanti; Ni Made Rai Wisudariani; Kadek Wirahyuni (Jurnal IKA, 2022)
The purposes of this qualitative descriptive study are (1) to describe the linguistic rules of the webtoon digital comic "Lucunya Hidup Ini", (2) to describe the implications of the webtoon digital comic "Lucunya Hidup Ini" as a medium for learning anecdotal texts at the high school level. The subject of this research is the digital comic Webtoon “Lucunnya Hidup Ini” episodes 20, 23,35, 42, 93, and 242.The object of this research is the linguistic elements of anecdotal texts in Webtoon digital comics and their implications as a medium for learning anecdotal texts. Methods of data collection in the form of note-taking methods and documentation methods. Data analysis techniques used are data reduction, data presentation, and drawing conclusions.The results show that (1) the digital comic Webtoon "Lucunya Hidup Ini" covering 6 episodes has found six linguistic elements of anecdotal texts contained in the form of past event sentences, rhetorical sentences, conjunctions, verbs, commands, and exclamations. This story is worthy of being used as a medium for learning anecdotal texts because it covers half of all linguistic elements of anecdotal texts. (2) The implication of using the webtoon digital comic "Lucunya Hidup Ini" as a medium for learning anecdotal texts at the high school level is very relevant to learning anecdotal texts because they contain the same linguistic elements. In addition, the “Lucunya Hidup Ini” Webtoon has the implication of triggering student interest in learning.